2019
DOI: 10.1021/acs.est.9b03358
|View full text |Cite
|
Sign up to set email alerts
|

Assessing NO2 Concentration and Model Uncertainty with High Spatiotemporal Resolution across the Contiguous United States Using Ensemble Model Averaging

Abstract: NO 2 is a combustion byproduct that has been associated with multiple adverse health outcomes. To assess NO 2 levels with high accuracy, we propose the use of an ensemble model to integrate multiple machine learning algorithms, including neural network, random forest, and gradient boosting, with a variety of predictor variables, including chemical transport models. This NO 2 model covers the entire contiguous U.S. with daily predictions on 1km-level grid cells from 2000 to 2016. The ensemble produced a cross-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
112
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 205 publications
(114 citation statements)
references
References 75 publications
0
112
1
1
Order By: Relevance
“…For the exposure, they calculated the mean of daily concentrations during 2010–2016 as modelled by a previously described ensemble machine learning model (R 2 =0·79). 25 They reported a 7·1% (1·2%–13·4%) increase in mortality per 4·5ppb (1ppb=1·25μg/m 3 ) increase in NO 2 after adjusting for confounders and spatial autocorrelation 9 (that is approximately 1·3% increase per 1 μg/m 3 ). The study in England, with partly overlapping data as in our analysis, also reported a significant association between NO 2 and COVID-19 mortality (p<0·05).…”
Section: Discussionmentioning
confidence: 98%
“…For the exposure, they calculated the mean of daily concentrations during 2010–2016 as modelled by a previously described ensemble machine learning model (R 2 =0·79). 25 They reported a 7·1% (1·2%–13·4%) increase in mortality per 4·5ppb (1ppb=1·25μg/m 3 ) increase in NO 2 after adjusting for confounders and spatial autocorrelation 9 (that is approximately 1·3% increase per 1 μg/m 3 ). The study in England, with partly overlapping data as in our analysis, also reported a significant association between NO 2 and COVID-19 mortality (p<0·05).…”
Section: Discussionmentioning
confidence: 98%
“…The study in the US focused on deaths reported by April 29, 2020, using 3122 counties. For the exposure, they calculated the mean of daily concentrations during 2010–2016 as modelled by a previously described ensemble machine learning model (R 2 = 0.79) ( Di et al, 2019a ). They reported a 7.1% (95% Confidence Interval: 1.2%, 13.4%) increase in mortality per 4.5 ppb (1 ppb = 1.25 μg/m 3 ) increase in NO 2 after adjusting for confounders and spatial autocorrelation( Liang et al 2020 )(that is approximately 1.3% increase per 1 μg/m 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work can make use of more spatially refined estimates of PM 2:5 (Di et al 2019). In addition, NO 2 satellite-derived models have now been developed (Di et al 2020) that can be compared with results from LUR models.…”
Section: Discussionmentioning
confidence: 99%